Heterozygous variants in the integrin subunit beta 4 gene (ITGB4) cause autosomal dominant nail dystrophy. (1st November 2022) - Malovitski, Kiril; Meijers, Odile; Cohen‐Barak, Eran; Bergman, James; Adir, Noam; Giladi, Moshe; Shalev, Stavit; Sarig, Ofer; Schwartz, Janice; Evans, Holly; Sprecher, Eli; Samuelov, Liat
Abstract: